COVID-19 research spread in Indonesia on social media - La Tarifu; Joko Joko; Cecep Ibrahim; Rahmat Fadhli; Sri Hartinah (Perpustakaan Universitas Gadjah Mada, 2022)
Introduction. The purpose of this study is to determine the impact of Indonesian COVID-19 research. One of them is productive author, productive citations, the most popular social media to disseminate research results, the most popular articles on social media, mapping or distribution of research results visualization, and the correlation of social media data with citations. Data Collection Method. The research data was taken from the Scopus database and this research use method Bibliometric, Altmetric, Scientometric, and linear regression tests. Data Analysis. The data of the study was analyzed using program (altmetric.com), VOSViewer and SPSS software. Result and Discussion. Pranata, R. was the productive author in producing Indonesian COVID-19 research. The University of Indonesia is the most productive institution. The study